DISCRETE MULTIVARIATE ANALYSIS USING LOG - LINEAR MODELS - J. Flowers, Robert (Ecosistemas y Recursos Agropecuarios, 2014)
a procedure is definid for obtaining maximun likelihood estimates for the parameters of a family of log - linear models which includes the general log - linear model, logit models, multinominal logit models, and association models as well as models for which maximium Para mas información, conunicarse al correo era@ujat.mx